(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
With the widespread adoption of internet technologies, concerns about internet addiction have grown. Media reports suggest that many students are no longer actively participating in educational activities as they should. This trend could negatively affect academic performance. This study investigated internet dependency as a factor influencing schoolwork engagement among secondary school students. A survey was conducted with 252 senior secondary school students from both public and private schools in River State. Participants completed self-report measures related to schoolwork engagement and smartphone addiction. The results of a simple regression analysis indicated that internet dependency significantly predicted schoolwork participation. This finding supports the hypothesis that internet dependency correlates with reduced engagement in school-related tasks. Practical implications and recommendations are discussed.